The Application of Communicative Language Teaching (CLT) to Improve the Grammar Ability - Abdullah Syukur (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2021)
This research presented the Application of Communicative Language Teaching (CLT) Method through Grammar Practice Activities to Improve the Grammar Ability of the Fifth Semester Students of Informatic Study Program, Faculty of Computer Engineering, Cokroaminoto Palopo University. The objective of this research was to find out the effectiveness of grammar practice activities in CLT method in improving the grammar ability of the the Fifth Semester Students of Informatic Study Program, Faculty of Computer Engineering, Cokroaminoto Palopo University. The instruments of the research were test and questionnaire. The result of the research shows that the highest percentage was 56.8% of samples got good in grammar comprehension. The analysis of the test showed that the application of grammar practice activities in CLT method is effective based on the coefficient level a = 0.05 / 5% = 2.045, the researcher found that the significance test of the pre-test and post-test result was 14.522. And based on the questionnaire, this application was effective with the calculation of percentage was 33.3% strongly agree, 6.7% was strongly disagree.